A Tudy of Impacts of the Use of Cost Information on Business Performance of Fishery Processing Enterprises in Vietnam - DANG, Lan Anh; LE, Thi Minh Hue (Archives of Business Research, 2022)
This study aims to examine the relationship between the Use of Cost Information (UCI) and the Business Performance (BP) of Fishery Processing Enterprises (FPEs) in Vietnam. The authors approach the needs of managers to use cost information in performing their functions of planning, business activities control, performance evaluation, and business decision making. By quantitative research method, using survey data from managers at FPEs, the authors examine the impact direction and level of impact of UCI on the BP these enterprises. From there, the author proposes solutions to improve the efficiency of using cost information for administrative purposes, in order to improve BP of FPEs.